(untitled) (Research, Society and Development, 2024)
Digital dentistry has promoted significant advances in aesthetic and orthodontic planning, providing greater precision and efficiency in treatments. This study aimed to review the scientific literature published between 2010 and 2024, and other specific ones, analyzing the impact of digital technologies on orthodontic diagnosis and treatment. Articles were selected from PubMed, SciELO and Google Scholar databases, focusing on technologies such as intraoral scanners, digital setup, cone beam computed tomography (CBCT), 3D printing, digital planning software and others. The analysis included only studies that discussed the practical application of these tools in the orthodontic context. The results highlight that digital dentistry has transformed orthodontic planning, making treatments more efficient, predictable and personalized, evidencing the positive impact of these innovations on clinical efficiency and patient comfort. Technologies such as digital setup, intraoral scanners, CAD/CAM systems and 3D printing have improved diagnostic visualization and communication with patients, in addition to optimizing the production of customized orthodontic devices. The use of these tools, although effective, presents challenges such as high implementation costs and the need for advanced technical training. However, the integration of these technologies promises a promising future for orthodontics, with the potential to further transform the field, being a fundamental pillar in the creation of harmonious and customized smiles.